Review of the genus Nysius Dallas from Mongolian Plateau (Hemiptera: Heteroptera: Orsillidae) - Ge, Xinyu; Li, Junlan (Zootaxa, 2019)
The genus Nysius Dallas (1852) from Mongolian Plateau is reviewed. Eight species are now recognized. Nysius ericae groenlandicus (Zetterstedt, 1838), known previously from Inner Mongolia, is referred to Nysius ericae ericae (Schilling, 1829). The paramere, pygophore, sperm reservoir and spermatheca of recorded species are illustrated. The distributional records of Nysius ericae ericae and Nysius thymi thymi (Wolff, 1840) are corrected. Photographs of adults, updated distribution maps and key for all species in Mongolian Plateau are provided.